Magnetic relaxation induced by transverse flux shaking in MgB2 superconductors - Nieva, Gladys (2009)
Fil: Luzuriaga, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina